2023
DOI: 10.1155/2023/3071610
|View full text |Cite
|
Sign up to set email alerts
|

Yiyi Fuzi Baijiang Powder Alleviates Dextran Sulfate Sodium-Induced Ulcerative Colitis in Rats via Inhibiting the TLR4/NF-κB/NLRP3 Inflammasome Signaling Pathway to Repair the Intestinal Epithelial Barrier, and Modulating Intestinal Microbiota

Abstract: Ulcerative colitis (UC) is a chronic non-specific inflammatory disease of the intestine, which is prone to recurrence and difficult to cure. Yiyi Fuzi Baijiang powder (YFBP), as a classic Chinese herbal formula, is commonly used in the clinical treatment of UC. However, its potential mechanism remains unclear. In this study, we investigated the mechanism by which YFBP exerts a therapeutic effect against UC. Firstly, we used network pharmacology to screen the active ingredients and potential targets of YFBP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…A large number of studies have shown that DSS-induced colitis mouse models can lead to a signi cant decrease in colon length and body weight, a signi cant increase in disease activity index (DAI) and severe damage to intestinal structure [22][23][24]. This is consistent with the results observed in this study.…”
Section: Discussionsupporting
confidence: 92%
“…A large number of studies have shown that DSS-induced colitis mouse models can lead to a signi cant decrease in colon length and body weight, a signi cant increase in disease activity index (DAI) and severe damage to intestinal structure [22][23][24]. This is consistent with the results observed in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the anti-UC function of JGQD were largely dependent on gut microbiota and might have the potential to application as a complementary medicine in UC treatment. Another study by Yang et al (2023) reported that Yiyi Fuzi Baijiang Powder (YFBP), a classic Chinese herbal formula commonly used in treating UC, might regulate the diversity and richness of intestinal microbiota and thus affect the severity of experimental colitis using a strategy combined with network pharmacology, screening, and bioinformatics.…”
Section: Traditional Medicine-derived Compounds Ameliorate Uc Via Var...mentioning
confidence: 99%
“…This study thus indicated the role of MKP1 in the regulation of the NLRP3 inflammasome and pyroptosis. In addition, as shown by Yang et al (2023) , Yiyi Fuzi Baijiang Powder (YFBP) could also be a decoction that affects the progression of colitis via regulating the NLRP3/pyroptosis pathway. YFBP is a classic Chinese herbal formula commonly used in treating UC.…”
Section: Traditional Medicine-derived Compounds Ameliorate Uc Via Var...mentioning
confidence: 99%
“…Yiyi Fuzi Baijiang Powder can slow down the progression of colorectal cancer by simultaneously regulating target genes and related signaling pathways of multiple active ingredients, possibly by regulating cell apoptosis, cell proliferation, and protein and enzyme binding[ 58 ], and this has been experimentally validated[ 59 ]. Yiyi Fuzi Baijiang Powder has a good effect in treating ulcerative colitis, can inhibit intestinal symptoms in mice, and improve intestinal pathology[ 60 ]. According to reports, Qingyi huaji decoction can be applied as a valid method to treat pancreatic cancer, and research has confirmed that it can inhibit the growth and progression of tumor through various mechanisms such as anti-inflammatory and induction of cell apoptosis[ 61 ].…”
Section: Application Of Coix Seedmentioning
confidence: 99%